2023
DOI: 10.1038/s41598-023-37461-x
|View full text |Cite
|
Sign up to set email alerts
|

3D-printing-assisted fabrication of hierarchically structured biomimetic surfaces with dual-wettability for water harvesting

Abstract: Freshwater acquisition methods under various environments are required because water scarcity has intensified worldwide. Furthermore, as water is an essential resource for humans, a freshwater acquisition method that can be utilized even under harsh conditions, such as waterless and polluted water environments, is highly required. In this study, a three-dimensional (3D) printing-assisted hierarchically structured surface with dual-wettability (i.e., surface with both hydrophobic and hydrophilic region) for fog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The ability of surfaces to efficiently drain water has become an area of significant interest due to their various applications in self-cleaning, 1,2 anti-fogging, 3,4 anti-icing, 5,6 heat transfer enhancement, 7 anti-splash, 8–11 creatural survival, 12–15 signal transmission 16 and liquid-based material manipulation. 17 Previous studies have focused on designing surfaces that increase driving forces 1,12,18–22 or reduce resistant forces 14,23–25 to achieve fast water removal or drainage. For instance, structures with larger asymmetry forces 12,18 or surfaces with wettability gradients 1,19,20 enhance the speed of water removal, superhydrophilic microwicks exploit stable liquid films to drain water rapidly by minimizing pinning forces, 14 and superhydrophobic needle nozzles help reduce the air–liquid–solid triple contact line, enabling faster and more precise dispensing of smaller droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of surfaces to efficiently drain water has become an area of significant interest due to their various applications in self-cleaning, 1,2 anti-fogging, 3,4 anti-icing, 5,6 heat transfer enhancement, 7 anti-splash, 8–11 creatural survival, 12–15 signal transmission 16 and liquid-based material manipulation. 17 Previous studies have focused on designing surfaces that increase driving forces 1,12,18–22 or reduce resistant forces 14,23–25 to achieve fast water removal or drainage. For instance, structures with larger asymmetry forces 12,18 or surfaces with wettability gradients 1,19,20 enhance the speed of water removal, superhydrophilic microwicks exploit stable liquid films to drain water rapidly by minimizing pinning forces, 14 and superhydrophobic needle nozzles help reduce the air–liquid–solid triple contact line, enabling faster and more precise dispensing of smaller droplets.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous studies have focused on designing surfaces that increase driving forces 1,12,18–22 or reduce resistant forces 14,23–25 to achieve fast water removal or drainage. For instance, structures with larger asymmetry forces 12,18 or surfaces with wettability gradients 1,19,20 enhance the speed of water removal, superhydrophilic microwicks exploit stable liquid films to drain water rapidly by minimizing pinning forces, 14 and superhydrophobic needle nozzles help reduce the air–liquid–solid triple contact line, enabling faster and more precise dispensing of smaller droplets. 23 Besides, external stimuli, such as electrical, 5,26–28 optical, 29 and magnetic 30,31 fields, have also been used to further enhance water drainage.…”
Section: Introductionmentioning
confidence: 99%
“…With the synergistic effect of the two, it promotes the transportation of droplets in the air from the tip of the cactus thorn to the root of the needle, which is quickly absorbed by the hairy body. , Researchers have dedicated considerable effort to the development of biomimetic cactus spines. For instance, the metal wires could be made to conical spine shape by gradient corrosion. However, this method is only suitable for some specific metals such as copper, titanium, and aluminum; 3D printing, electrospinning, and laser-cutting are alternative technologies for preparing biomimetic cactus spines. However, these approaches often come with drawbacks, such as complex procedures, challenging operations, and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability of both the biomimetic conical spines and the substrates integrated with them is a vital factor that directly influences the efficiency of fog capture. ,, In terms of wettability, enhancing of the hydrophobic properties of substrate materials can optimize the mobility of Cassie droplets, significantly diminish contact angle hysteresis, and facilitate the efficient transport of droplets . While hydrophobic substrates can enhance surface renewal and facilitate droplet mobility, superhydrophobic surfaces present a substantial energy barrier that impedes the initial capture of fog droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, innovative techniques have been utilized to create smart wettable materials that can reversibly switch wetting behavior . Switchable wettability has emerged as an interesting research direction because of its significance in applications such as self-cleaning, microfluidic devices, water collection, and oil–water separation. Choi et al fabricated a dual-wettability surface using 3D assisted printing. They concluded that hierarchically structured surfaces balanced the main performance combination to optimize the laplace pressure, surface area, and drainage efficiency.…”
Section: Introductionmentioning
confidence: 99%